Management of Chloridea virescens (Noctuidae) in blueberries (Vaccinium corymbosum L.) to promote sustainable cultivation in Peru: A Review - Narrea Cango, Mónica (2022)
A review of current and specific literature was carried out in order to elaborate a proposal for the management of Chloridia virescens in the cultivation of blueberry (Vaccinium corymbosum L.), developing strategies in each component of Integrated Pest Management (IPM), including Cultural Control, Ethological Control, Biological Control, and Chemical Control (PBUA and PQUA). Likewise, steps in the genetic improvement for quantitative resistance of the blueberry to this pest (Lepidoptera: Noctuidae) using wild relatives of this crop as a source of resistance genes are proposed.